Evaluation of increased microRNA-21 in the serum of patients with cardia cancer: MiR-21 in serum of cardia cancer patients - He, Longhai; Zhou, Yue (Cellular and Molecular Biology, 2022)
MicroRNAs are a new group of regulatory RNAs that are about 22 nucleotides long. MicroRNAs are also involved in many human cancers and can actually act as oncogenes and suppressors. In this study, the relationship between miR-21 levels in the serum of sick and healthy individuals and the relationship between high concentrations of this microRNA and tumor staging and cancer progression was performed for the first time in Iran on gastric cardia cancer. This study was performed on 40 patients with gastric cardia cancer and 40 patients who were selected as a control group. The control group was selected from those who presented due to gastrointestinal disorders but were diagnosed as healthy or non-cancerous. Their serum miR-21 was measured using the Real-Time PCR technique. The relationship between the concentration of this microRNA in serum with tumor staging and cancer progression was evaluated. Findings showed that increasing the concentration of miR-21 in serum samples, serum miR-21 in patients was about 3.5 times that of controls (P <0.0001), and serum miR-21 in patients was significantly related to staging tumor showed (P = 0.01), indicating a significant and direct relationship between miR-21 and tumor growth, which indicates the importance of this microRNA in the progression of gastric cancer. Given the role of miR-21 in the progression of gastric cardia cancer and its association with clinic-pathological factors, it can be introduced as a new diagnostic marker. It can also be used as a non-invasive method in the early diagnosis of gastric cancer patients. In this study, miR-21 has an oncogenic role that can be measured in patients' serum to assess the progression of gastric cancer.